ANALISIS PENERAPAN SISTEM AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. YUDHISTIRA GHALIA INDONESIA CABANG RANTAU PRAPAT (2023) - Nurlela; Bilia, Dea Salsa (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
The purpose of the research made by the researcher is to determine the application of the accounting system for cash receipts and cash disbursements at PT Yudhistira Ghalia Indonesia Rantau Prapat Branch. The data analysis method used in this research is qualitative method. The research data source is internal data. The type of data used is primary data collected through interviews, observation and documentation. From the results of the study, it shows that the application of the accounting system for cash receipts and disbursements applied by PT Yudhistira Ghalia Indonesia Rantau Prapat Branch is good which can be seen in the documents used that have sequential numbers, the cash recording system uses the MIS System to produce financial reports, work procedures seen from the flowchart. The cash recording system has been implemented through the Daily cash report. The accounting system for cash receipts and disbursements is supervised and controlled by the branch head or the authorized party (SUMUT branch head office), but there is no separation between cash and accounting functions and there is a delay in reporting book sales transactions including cash sales transactions, so that there are obstacles to the cash recording and reporting system to the SUMUT branch head office.